Present biodiversity status of loaches in the selected Hill-streams of Bangladesh - Akand, Md Kamrul Hasan; Hossain, Mostafa Ali Reza; Islam, Md Shariful (Research in Agriculture Livestock and Fisheries, 2015)
A year-long survey was conducted to study the biodiversity status of freshwater loaches of Bangladesh. Data and sample collection were carried out in the hill-streams of Bangladesh in the three districts namely Sylhet, Netrokona and Dinajpur. Fish samples were also collected from Mymensingh district. The study was based on fish landing centre and fish market visit, on the spot data collection, interview of the fishermen and the fish traders, sample collection and secondary data collection. During the study, 12 loaches under 2 families were found. Among the collected loaches 8 are exclusively used as food fish and the rest 4 species can be considered as both food fish and ornamental fish. Among the total number of species found during the study, 2 loaches were threatened based on IUCN Red List. Among the loaches recorded in the survey, 2 are endangered (EN), 3 data deficient (DD) and 7 not threatened (NO). Among the collected loaches Botia dario, Botia lohachata and Lepidocephalichthys annandalei were very rare. The non-availability and less availability of some of the species indicate the alarming decline of the biodiversity of loaches in the surveyed area and in the country as a whole. Res. Agric., Livest. Fish.2(2): 329-334, August 2015